If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(-8+6x)=22+3x
We move all terms to the left:
7(-8+6x)-(22+3x)=0
We add all the numbers together, and all the variables
7(6x-8)-(3x+22)=0
We multiply parentheses
42x-(3x+22)-56=0
We get rid of parentheses
42x-3x-22-56=0
We add all the numbers together, and all the variables
39x-78=0
We move all terms containing x to the left, all other terms to the right
39x=78
x=78/39
x=2
| 2.64=q+8.2 | | m-21=9 | | -9+7(r-1)=-9-4(r-1) | | 24x^2=90 | | 2x-4x=5(x-9)-4 | | -3+10u=2u+7+9u | | 3x+4x+8x=180 | | 2|m-3|=4 | | 0=5x^2+2x-7 | | -(8b-3)=-4(5-2b)-9 | | -3(2x+4)=36 | | 15+5.50x=196.50 | | -7(5-x)=3(x+7) | | 5(3x+6)=-17+32 | | s/3=1.2 | | |3x+5|=12x+8 | | 72+4+-14x=36 | | 5(m-5)=10(m+7) | | s/3=1.3 | | -2=7=x/11 | | H=-16t2+28t+3 | | 9+3/5x=10 | | 4x+16+56=11x-2 | | 3x+-9=3x+-9 | | 7z+35=42 | | 5.5d=23.1 | | 3x+11+5x-17=180 | | -4.9t^2+9t-3=0 | | Y/x+6+1=4x/x+6 | | 9x+5-3x=2(9x+6)-7 | | 24x=17x+21 | | -5p+p=-4(p-6)-2(4-2p) |